Pension Funds and Emerging Markets - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2004)
This paper focuses on the investment behavior of pension funds in developed and emerging market countries. First, it analyzes the main determinants of the emerging market asset allocation of pension funds in developed countries. Second, it assesses how pension funds in emerging markets have contributed to the development of local securities markets. Third, it analyzes the determinants of pension funds' investment performance. The paper concludes with a discussion of why the emerging market asset allocation of pension funds in developed countries is likely to increase and what the challenges faced by pension funds in emerging markets are.